A Proposed Project of Using Polypropylene (Pp) in Disposable Face Masks as an Additive to a Plastic Lumber: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A disposable face mask is essential to life. It has become mandatory to wear it everywhereand at all times, specifically during this pandemic. However, while protecting us from viruses, itcreates another problem that has an effect on the environment. Furthermore, the production ofplastic materials from plastic waste is becoming increasingly popular in the industry. In thePhilippines, there are social enterprises that collect plastic waste and turn it into new productsthat can be used in construction and home furnishings. To address the aforementioned issue,using disposable face masks as an additive in the production of plastic lumber could be a wayto reduce the amount of face mask waste that accumulates and advocate for a change to fightthe face mask waste problem.The results of the study in terms of structural composition are agreed upon by the civilengineers and strongly agreed upon by the architects. In terms of the procedural process,both civil engineers and architects strongly agree. In terms of the testing method in the weightplacement test, both civil engineers and architects strongly agree. It indicates that there are nosignificant differences between the assessments of the two groups of respondents in terms ofstructural composition, procedural process, and testing method in the weight placement test.The civil engineers obtained a 3.55 overall weighted mean and the architects a 3.62. With avariance of 0.108 in civil engineers and 0.016 in architects. The T-critical value is 2.776, andthe T-computed value is 0.380. Therefore, it accepts Ho.For further enhancement and improvement of the project, the ensuing discussions and therecommendations proposed in terms of structural composition and procedural process are asfollows: gathering the plastics and adding more facemasks that are shredded.
Keywords: Engineering